2018
DOI: 10.1111/ajco.13103
|View full text |Cite
|
Sign up to set email alerts
|

The effects of switching EGFR‐TKI treatments for non‐small cell lung cancer because of adverse events

Abstract: Background Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are used to treat patients with non‐small cell lung cancer (NSCLC) and EGFR driver mutations. Although some patients discontinued these treatments because of adverse events, it is unclear whether switching EGFR‐TKI because of adverse events provides a benefit. Methods This retrospective study evaluated data from 22 patients with EGFR mutation‐positive NSCLC who received at least two EGFR‐TKIs that were switched because of advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In contrast, among patients who experienced drug discontinuation, a similar trend of no differences among EGFR-TKIs was found for PFS but not for OS, which might be influenced by the sequential treatment with other EGFR-TKIs [29,30]. These findings should be carefully interpreted, as a limited proportion of patients experienced either dose adjustment or drug discontinuation in the current cohort, except in the 40 mg afatinib group due to the higher level of AEs compared with other EGFR-TKIs [24].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, among patients who experienced drug discontinuation, a similar trend of no differences among EGFR-TKIs was found for PFS but not for OS, which might be influenced by the sequential treatment with other EGFR-TKIs [29,30]. These findings should be carefully interpreted, as a limited proportion of patients experienced either dose adjustment or drug discontinuation in the current cohort, except in the 40 mg afatinib group due to the higher level of AEs compared with other EGFR-TKIs [24].…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, hepatotoxicity was the main reason of drug switching in EGFR–TKI treatments 44 . In previous clinical case reports, several case studies suggested that erlotinib was a well-tolerated and effective alternative treatment option for patients suffered from gefitinib-induced hepatotoxicity 3 , 25 , implied that the mechanisms of hepatotoxicity induced by gefitinib/erlotinib might be different.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in targeted therapy of malignant lung tumors have been led by the development of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) which are widely applied in the clinic as the standard first-line option for treating EGFR-mutant NSCLC with category 1 recommendations 8 . Gefitinib (Gef) induces apoptosis by targeting the ATP cleft to prevent EGFR autophosphorylation 9 and has a high clinical benefit 10 .…”
Section: Introductionmentioning
confidence: 99%